Wearable Multifunctional Graphene‐Based Aerogel/Spacer Fabric Composites for Sensing and Impact Protection. Issue 9 (30th March 2022) - Wang, Shu; Ning, Huiming; Liu, Feng; Hu, Ning; Zhang, Hao; Zou, Rui; Wen, Jie; Huang, Kaiyan; Wu, Xiaopeng; Song, Zengrui; Xiang, Chenxing; Wang, Ziying
Abstract: A multifunctional composite composed of a spacer fabric and a porous graphene‐based aerogel is proposed for sensing and impact protection applications. The combination of the mechanical properties of the spacer fabric and the electrical properties of the graphene‐based aerogel provides a versatile composite material with a strain sensitivity of 1.48, a temperature sensitivity of −0.004 °C −1, and a protection factor of 45%. The material is also lightweight, hydrophobic, and thermally insulating. It is therefore suitable for both high‐temperature (nearly 180 °C) and low‐temperature applications. Consequently, the developed multifunctional composite has potential for use as a building material and as a smart cushion for healthcare. Abstract : In this work, an aerogel/spacer fabric composite is fabricated by a simple method, which has a strain sensitivity of 1.48 and a temperature sensitivity of −0.004 °C −1 within the temperature range 32–114 °C. It is lightweight, hydrophobic, thermally insulating, and capable of providing impact protection. Therefore, it is a promising material for healthcare applications, smart cushions, and building material.